Process Or Product? Academic Writing in a Changing Tertiary Environment - Coleman, Patrick (CIEX JOURNAL, 2025)
The internationalisation of education has placed English language teachers at the forefront of preparing students for tertiary study, with applied linguistic research guiding their practices. Two common academic writing approaches are the product-based approach, focusing on language replication, and the process-based approach, emphasising writing processes. Digital technology, especially AI tools like ChatGPT, has significantly influenced academic writing instruction. While some view these tools as challenges, others see opportunities to enhance learning. This presentation will explore these approaches, the impact of Gen AI, and provide examples from a New Zealand EAP pre-degree programme to assist teachers and students.